PENERAPAN METODE PEMBELAJARAN SQ4R UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA DASAR - Fadillah, Ahmad Arif; Rosadah; Fazriah, Nurul; Ilyasa, Nabila; Nahzifa, Nanda; Nurahmah, Suci; Pratami, Santika Vidia; Putri, Ratasya Salsabilla; Uthantry, Zuanita Hershifani (Transpublika Publisher, 2022)
This study aims to analyze the application of sq4r learning methods to improve the reading skills of basic students. The design of this study is PTK. Research activities are carried out in 2 (two) cycles, each cycle lasts 2 hours of lessons (2 x 45 minutes). Each cycle includes stages: 1) planning, 2) execution of actions, 3) observation and evaluation, 4) analysis and reflection. This research was carried out at SDN Negeri 1 Gadang. The class studied was class V with a total of 36 students. Based on the results of the research described, it can be concluded that by applying the stages of the Survey, Question, Read, reflect, Recite, Review (SQ4R) learning model in the learning process can increase teacher learning activities and student learning activities during the learning process in class V of SDN Negeri 1 Gadang. Changes in the learning process that occur encourage the improvement of student learning outcomes related to reading comprehension material in Indonesian subjects in class V of SDN Negeri 1 Gadang.